A challenging case of a chyle leak following axillary lymph node clearance. Issue 8 (22nd August 2020) - Wong, Joshua; Farkas, Nicholas; Monib, Sherif; Thomson, Simon
Abstract: Chyle leak following axillary lymph node clearance is a rarely reported complication. We present a case of chylous leakage following axillary lymph node clearance, which was diagnosed on clinical grounds. Surgical re-exploration was undertaken due to ongoing high output. However, the chylous leak recurred post-operatively, if at a lower rate. The patient was subsequently managed successfully with conservative measures, primarily utilizing regular aspiration and compression bandaging to the axilla.